Assessing platelet reactivity after drug eluting stent implantation: state of the art. (2nd January 2020) - Tantry, Udaya S.; Timilsina, Saroj; Rout, Amit; Bliden, Kevin; Gurbel, Paul A.
ABSTRACT: Introduction : Platelets play a pivotal role in the occurrence of recurrent ischemic events in coronary artery disease patients who are treated with drug-eluting stents and are on dual antiplatelet therapy (DAPT). Areas covered : High platelet reactivity (HPR) to adenosine diphosphate during clopidogrel therapy is a strong predictor of post-stenting ischemic event occurrences. However, uniform use of potent P2Y12 receptors blockers to overcome HPR is associated with elevated bleeding risk. Selective de-escalation of P2Y12 receptor blocker therapy based on PFT in patients with acute coronary syndrome treated with stenting has been shown to be associated with a similar risk of ischemic event occurrence but with a reduced risk of bleeding. This review aims to discuss the role of PFT in guiding DAPT in patients treated with DES. We searched electronic databases from January 2000 to December 2019 for literatures evaluating the role of platelet function assessment after drug eluting stents. Expert opinion : Platelet function guided therapy improves patient outcomes by lessening bleeding and limiting the overuse of highly potent P2Y12 inhibitors. Interest in this area of de-escalation of therapy will likely grow as the consequences of bleeding are better recognized and the cost of healthcare gains greater focus.